Flypaper [videorecording (DVD)] - Dempsey, Patrick, 1966-; Judd, Ashley; Nelson, Tim Blake (IFC Films, 2011)
A nervous bank customer has a crush on beautiful teller. They and the other staff and customers become hostages when two very different groups of crooks hit the bank simultaneously. When people begin mysteriously dying one by one, everyone involved begins to wonder if there's someone else in the bank up to no good.